2018
DOI: 10.1176/appi.ps.201700492
|View full text |Cite
|
Sign up to set email alerts
|

What Clinicians Say About the Experience of Working With Individuals on Community Treatment Orders

Abstract: Clinicians view CTOs as providing benefits to their clients but struggle with the coercive nature of these tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
(45 reference statements)
2
10
0
Order By: Relevance
“…Consistent with previous qualitative research in Australia and elsewhere, service providers, family supporters, and consumers shared many similar perceptions regarding the experience of CTOs, as well as a mixed and often ambivalent stance about CTOs (10, 11, 25, 26). Most consumers described CTOs as wholly negative; both the process of being placed on a CTO and its impact.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with previous qualitative research in Australia and elsewhere, service providers, family supporters, and consumers shared many similar perceptions regarding the experience of CTOs, as well as a mixed and often ambivalent stance about CTOs (10, 11, 25, 26). Most consumers described CTOs as wholly negative; both the process of being placed on a CTO and its impact.…”
Section: Discussionsupporting
confidence: 72%
“…They lead to a restriction of human rights including the rights to liberty and physical and mental integrity sometimes over many years, and evidence about their effectiveness remains weak despite randomized control trials (5, 8, 9). Corring et al (10, 11) have undertaken reviews of qualitative studies on the experience of people on CTOs and suggest that there are common themes among people on CTOs and clinicians (10, 11). They may, for example, see CTOs as helpful but remain concerned about the ethical and human rights implications of their use.…”
Section: Introductionmentioning
confidence: 99%
“…Norwegian and international studies show that CTOs are often founded on patients’ lack of insight, to prevent psychotic relapse [ 12 ], which often has a disruptive effect on people’s quality of life and their capacity for independence. A Norwegian study showed that CTO practices vary [ 19 ] and that some RCs only met patients at yearly reviews, knew little about the content of local care services and the impact of CTOs on patients’ everyday lives.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing discussion as to whether the mandatory element of the CTO produces greater clinical benefits for patients than offering them the same package of services on a voluntary basis [ 5 , 10 , 11 ]. International and Norwegian studies show that the use of CTOs is often justified on the basis of patients’ lack of illness insight [ 12 ], and that they are mainly used to provide support and treatment following involuntary hospital admissions [ 12 14 ]. Studies show that patients have mixed views of coercion in general and CTOs in particular, while psychiatrists and patients’ relatives are more positive [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…First-generation compounds tend to be cheap while second-generation compounds tend to be expensive. Many states in the USA and some other countries 54 offer involuntary outpatient or community treatment laws that may facilitate the use of LAIs, but these forced outpatient treatment orders are not present in many European countries which, on the other hand, offer easy access to free psychiatric treatment including free medications.…”
Section: Measuring Medication Adherence In Psychiatrymentioning
confidence: 99%